2021
DOI: 10.1002/jsfa.11557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high wave sound pretreatment on drying quality parameters of echinacea root with infrared drying

Abstract: BACKGROUND Echinacea is a perennial and herbaceous herb containing the most active phenolic compounds and valuable antimicrobial and antioxidant content, such as chicoric acid, which increases the body immune function. The root of this plant is mainly used in pharmaceutical fields to treat inflammation, kidney infections and colds. In the present study, we investigated the drying of echinacea root in an infrared dryer with airborne ultrasonic pretreatment aiming to determine shrinkage, color changes, extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The quadratic effect of the MP on the D eff of blanched and ultrasonicated samples was significant (p < 0.0001), while it was not significant in the controls. Equations ( 11), (17), and ( 23) in Table 2 show the model of the D eff variations in relation with the independent parameters. According to the model coefficients, the influence of the MP was higher than the effect of the ST on the D eff value of the pretreated samples.…”
Section: Effective Moisture Diffusivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The quadratic effect of the MP on the D eff of blanched and ultrasonicated samples was significant (p < 0.0001), while it was not significant in the controls. Equations ( 11), (17), and ( 23) in Table 2 show the model of the D eff variations in relation with the independent parameters. According to the model coefficients, the influence of the MP was higher than the effect of the ST on the D eff value of the pretreated samples.…”
Section: Effective Moisture Diffusivitymentioning
confidence: 99%
“…Diverse methods have been developed for optimization, among which is the response surface method (RSM). In the RSM, the relationship between the response and independent variables can be determined through mathematical modeling [17]. Numerous studies have optimized and modeled the impact of the drying variables (such as air speed and temperature, microwave power (MP), and slice thickness (ST)) on the response parameters including mechanical and thermal qualities as well as the quality of the agricultural products such as cumin seeds [18], sweet potato slices [8], and Cornus mas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of IR drying include drying many chemicals, pharmaceuticals and food in industry, and performing laboratory tests to determine the drying characteristics of various materials. Many herbs and medicinal roots, including ginseng (Xiao et al, 2014), peppermint leaves (Ashtiani et al, 2017), aloe vera (Sriariyakul et al, 2016), pakchoi (X. F. Wu et al, 2019), black tea (Qu et al, 2019), peppermint leaves (Torki-Harchegani et al, 2016), and so on, which were dried with an IR dryer, indicated the maximum preservation of their active ingredients compared to other dryers (Rostami et al, 2022).…”
mentioning
confidence: 99%
“…It was measured using a digital and portable colorimeter device (model CR 400, Konica Minolta, Japan). L *, a *, and b * variables of the CIELAB color space were measured using the device, representing brightness (0 = black, 100 = white), color axis from green (−) to red (+), and from blue (−) to yellow (+) is defined (Rostami Gharkhloo et al., 2022; Taghinezhad et al., 2023). The chroma ( C ) and total color difference (Δ E ) values were obtained using Equations (7) and (8), respectively (Akhoundzadeh Yamchi et al., 2024; Qing et al., 2023).…”
Section: Methodsmentioning
confidence: 99%